Development on Infected Citrus over Generations Increases Vector Infection by ‘Candidatus Liberibacter Asiaticus in Diaphorina citri’ - Inaiara de Souza Pacheco; Diogo Manzano Galdeano; João Roberto Spotti Lopes; Marcos Antonio Machado (Insects, 2020)
‘Candidatus Liberibacter asiaticus’ (CLas) is a major causal agent of citrus Huanglongbing (HLB), which is transmitted by Asian citrus psyllid (ACP), Diaphorina citri, causing severe losses in various regions of the world. Vector efficiency is higher when acquisition occurs by ACP immature stages and over longer feeding periods. In this context, our goal was to evaluate the progression of CLas population and infection rate over four ACP generations that continuously developed on infected citrus plants. We showed that the frequency of CLas-positive adult samples increased from 42% in the parental generation to 100% in the fourth generation developing on CLas-infected citrus. The bacterial population in the vector also increased over generations. This information reinforces the importance of HLB management strategies, such as vector control and eradication of diseased citrus trees, to avoid the development of CLas-infected ACP generations with higher bacterial loads and, likely, a higher probability of spreading the pathogen in citrus orchards.